Modern sedative agents and techniques used in dentistry for patients with special needs: A review - Yang, R.; Zhao, R.; Chaudry, F.; Wang, T.; Brunton, Paul; Khurshid, Z.; Ratnayake, J. (2024)
According to the World Health Organisation, approximately 1.3 billion people worldwide experience substantial disability due to physical, mental or sensory impairment. People with special needs require special consideration and more time or altered delivery methods when receiving dental treatments. Various factors, such as patients' lack of cooperation, cognitive impairment and complex medical status, may lead dental practitioners to recommend conscious sedation. Several pharmacological agents and administrative routes are available, which achieve varying levels of sedation ranging from minimal to deep. Pre-operative assessment and careful case selection are necessary to determine the appropriate sedative agent, route of administration and level of sedation for each patient. Thus, a thorough understanding of the pharmacokinetics, risks and benefits, and implications of various sedatives available for PSN is essential to achieve the desired clinical outcomes. This review critically presents the considerations associated with the use of various sedative agents for PSN in dentistry. Considerations include patients' pre-anaesthesia medical comorbidities, cardiorespiratory adverse effects and cooperativeness, and the viable alternative treatment modalities.